Cybersecurity: From Months to Milliseconds. - Fonash, Peter; Schneck, Phyllis (Computer (00189162), 2015)
Computer technology is the nexus of our critical infrastructures, yet it remains extremely vulnerable to cyberattacks. A proposed Integrated Adaptive Cyber Defense architecture promises to create a healthy cyber ecosystem by automating many risk decisions and optimizing human oversight of security processes too complex or important for machines alone to solve.